Identify key transcript factors of adipocyte differentiation in abdominal fat of broilers based on ATAC-seq and RNA-seq - Xiaoying Liu; Chaohui Wang; Xi Sun; Zhihao Qiao; Xiaojun Yang; Yanli Liu (Poultry Science)
Intensive breeding has resulted in excessive deposition of abdominal fat tissue (AFT) in broilers, leading to significant economic loss in the poultry industry. Understanding the molecular mechanisms underlying AFT development is essential for informed breeding strategies. In the current study, we elucidated dynamic changes of chromatin accessibility and transcriptional reprogramming in AFT at D14 and D42 in broilers based on integrated analysis of RNA-seq and ATAC-seq. RNA-seq analysis manifested significant transcriptional differences in AFT development, identifying 1323 up- and 1285 down-regulated differential expression genes (DEGs) as well as 63 up- and 58 down-regulated transcription factors (TFs) at D42 compared to those at D14. Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis of total DEGs revealed significant enrichment in pathways related to DNA replication, cell adhesion molecules, cell cycle, p53 signaling pathway, fatty acid degradation, fatty acid biosynthesis and steroid biosynthesis. Gene set enrichment analysis (GSEA) further indicated that autophagy, MAPK signaling pathway and inositol phosphate metabolism were up-regulated at D42 compared to D14, whereas cell cycle, DNA replication and steroid biosynthesis were down-regulated. Additionally, ATAC-seq analysis identified 394 gain and 1195 loss differentially accessible peaks (DPs) in AFT between D14 and D42, associated with 319 and 905 genes, respectively. These gain or loss genes were enriched in p53 signaling pathway, PPAR signaling pathway, fat digestion and absorption, FoxO signaling pathway and glycerol lipid metabolism. Integration analysis of ATAC-seq and RNA-seq data revealed 25 up-regulated and 75 down-regulated DEGs overlapping with genes linked to gain and loss DPs, respectively. Notably, ACACA, SCD, SREBF1and KLF9 exhibited significantly lower expression at D42 compared to D14. DNA motifs analysis identified NFIX and MYB as loss motifs, overlapping with down-regulated TFs, suggesting their potential role in AFT regulation. Furthermore, MYB and NFIX exhibited potential binding sites in the promoter regions of lipid metabolism-related genes (ELOVL6, PPARγ, FABP4, ACACA and SCD). Overall, these results will provide a theoretical basis for investigating the epigenetic modification and transcriptional regulation of AFT development in broilers.